Wealth Taxation of Real Estate During the Greek Crisis: The Perils of Ignoring Market Signals - Dimitris Christelis (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
During the Greek crisis the wealth tax on real estate (WTRE) was increased four-fold as a percentage of GDP in order to boost fiscal revenues. This increase contributed to an essentially complete freeze of the real estate market, a considerable drop in real estate prices, and a substantial deepening of the recession. Using conservative assumptions, we calculate that the WTRE increases unemployment by 70,000-100,000 persons yearly. Perversely, the net effect of the WTRE increase on fiscal revenues has been, at best, slightly positive if not quite negative, as the WTRE induces large tax losses by lowering household spending and housing investment. Moreover, the real estate market freeze prevents households from accessing their savings embodied in real estate in order to counter the recession's negative effects, and pay taxes and other debts. Reasons for this policy failure include flawed economic analysis, failure to monitor the real estate market, and cognitive biases.
Keywords: H20; H31; D14; E21; E22; E62; 330; Wealth tax; real estate; market collapse; liquidity constraints; multiplier; Greek crisis